2021
DOI: 10.3390/app11104506
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained Estimation of Multitype Car Rental Demand

Abstract: The unconstrained demand forecast for car rentals has become a difficult problem for revenue management due to the need to cope with a variety of rental vehicles, the strong subjective desires and requests of customers, and the high probability of upgrading and downgrading circumstances. The unconstrained demand forecast mainly includes repairing of constrained historical demand and forecasting of future demand. In this work, a new methodology is developed based on multiple discrete choice models to obtain cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…RM has become part of public research themes from the late 1980s, and many models and business instance reports have been illustrated over the past 30 years in various perishable assets industries. [3,4,5,33,6,8,9,12,13,15,11,7,10,14]. A study on airline tickets among them showed that a 20% improvement in the accuracy of quantity demand forecasting led to a 0.5-3% increase in revenue.…”
Section: Historymentioning
confidence: 99%
See 3 more Smart Citations
“…RM has become part of public research themes from the late 1980s, and many models and business instance reports have been illustrated over the past 30 years in various perishable assets industries. [3,4,5,33,6,8,9,12,13,15,11,7,10,14]. A study on airline tickets among them showed that a 20% improvement in the accuracy of quantity demand forecasting led to a 0.5-3% increase in revenue.…”
Section: Historymentioning
confidence: 99%
“…From Eqs. ( 8), (9), and (10), the function 𝜙 is uniquely determined as the exponential decay function 𝜙(𝑡; 𝛽) = exp(−𝛽𝑡) (see the supplemental document for an explanation), and we consequently obtain the formula about average booking curves: E[𝑋 (𝑡)] = 𝐴 exp(−𝛽𝑡). Note that a differential equation 𝑑 𝜙 (𝑡) 𝑑𝑡 = −𝛽𝜙(𝑡), which implies the property that an increase in the sums of bookings is proportional to the number of cumulative bookings, as is shown in the explanation document.…”
Section: Averaging Daily Booking Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…For over 30 years, the perishable assets industry, comprising hotels and airline ticketing, has utilized revenue management (RM) to manage inventory over a finite sales horizon to maximize profits 1 5 . The application fields have been diverse 6 , 7 such as car rentals 8 , 9 , golf 10 , 11 , cruise lines 12 , 13 , railway tickets 14 , theme parks 15 . The cumulative time series of bookings represent a booking curve.…”
Section: Introductionmentioning
confidence: 99%